The glandular odontogenic cyst: a case report. - de Carvalho, Y. R.; Kimaid, A.; Cabral, L. A.; Nogueira, T. O. (My University, 1994)
A case of a glandular odontogenic cyst is reported. All clinical, radiographic, and histopathologic features are discussed and compared with the descriptions in the literature already published about this new lesion.
Keywords: adult; case report; female; human; jaw disease; odontogenic cyst; pathology; salivary gland disease; Case Report; Female; Human; Mandibular Diseases; Middle Age; Odontogenic Cysts; Salivary Gland Diseases